Macrolide Resistance and Its Molecular Genetic Mechanisms in Streptococcus pyogenes Isolated from Children - L. K. Katosova; A. V. Lazareva; T. A. Khokhlova; O. A. Ponomarenko; N. M. Alyabieva (Антибиотики и Химиотерапия)
The frequency and mechanisms of resistance to macrolides in Streptococcus pyogenes isolated within 3 periods: 2011-2012 (246 strains), 2013-2014 (273 strains) and from January to November of 2015 (120 strains) were studied. The strains of S.pyogenes (639) were isolated from 17107 nasopharyngeal, vaginal and middle ear discharge smears of children on their visits to physiciants or hospitalization at somatic hospital departments. The susceptibility was tested by the disk diffusion method and E-test strips. Identification of the mechanisms of resistance to macrolides and lincosamides included phenotypic and molecular genetic methods. PCR was used to determine ermB and mef genes in 23 erythromycin resistant isolates. As compared to 2011-2012, resistance of S.pyogenes to macrolides increased from 5 to 16% in 2015 and that to clindamycin from 2 to 10%. Among 23 erythromycin resistant strains 6 (26.1%) belonged to the M phenotype, 3 (13.0%) belonged to the iMLSb phenotype and 14 (60.9%) belonged to the сMLSb phenotype. The results of detecting the macrolide resistance genes in S.pyogenes showed that only 26.1% of the isolates expressed the mefA gene. The predominant share (65.2%) of the erythromycin resistant isolates possesed the ermB gene as a determinant and in 4.3% of the isolates the ermB gene was associatied with the mef gene. No resistance genes were detected 1 isolate. Therefore, the main mechanism that determined resistance of S.pyogenes to macrolides was methylation of ribosomes mediated by the ermB gene.